Respostas
respondido por:
7
5x²-10x-5=0
Simplificando por 5
x²-2x-1=0
a= 1 b=-2 c= -1
Δ= (-2)² - 4·1·(-1)
Δ= 4+4
Δ= 8
x= -b +/-√Δ/2a
x= -(-2) +/-√8/2·1
x= 2+/-√8/2
x'=-2√2
x''= 2√2
S:[ -2√2, 2√2]
Simplificando por 5
x²-2x-1=0
a= 1 b=-2 c= -1
Δ= (-2)² - 4·1·(-1)
Δ= 4+4
Δ= 8
x= -b +/-√Δ/2a
x= -(-2) +/-√8/2·1
x= 2+/-√8/2
x'=-2√2
x''= 2√2
S:[ -2√2, 2√2]
respondido por:
5
5x²-10x-5=0
podemos simplificar dividindo todos os valores por 5.
x²-2x-1=0
a=1 b=-2 c=-1
Δ=b²-4ac
Δ=(-2)²-4.1.(-1)
Δ=4+4
Δ=8
x=-b+-√Δ/2a
x=-(-2)+-√8/2.1
x=2+-√8/2
x'=2+√8/2 =>x'=-2√2
x''=2-√8/2=> x''=2√2
S{-2√2,2√2}
podemos simplificar dividindo todos os valores por 5.
x²-2x-1=0
a=1 b=-2 c=-1
Δ=b²-4ac
Δ=(-2)²-4.1.(-1)
Δ=4+4
Δ=8
x=-b+-√Δ/2a
x=-(-2)+-√8/2.1
x=2+-√8/2
x'=2+√8/2 =>x'=-2√2
x''=2-√8/2=> x''=2√2
S{-2√2,2√2}
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás